Survey Perkuliahan Pembelajaran Olahraga Jasmani Dan Kesehatan Pada SD Berbasis E-Learning - Haryanto, Andung Dwi (STAMINA, 2023)
Corona virus disease or covid-19 has spread to various countries and has hampered activities in various fields including education. In order to reduce the spread of Covid-19, the government adopted a policy of switching learning to be implemented online. Likewise with MI/SD physical sports and health learning lectures which are carried out online using e-learning learning media. The purpose of this study was to find out the lecture process for physical sports and health in MI/SD and to find out the evaluation of e-learning learning media used in online lectures. This type of research is descriptive research with a quantitative approach. The respondents used were the entire population, namely all students who attended lectures on physical sports and health in MI/SD, totaling 132 students and divided into 5 classes. The results show that at the planning stage a percentage of 76.86% is included in the good category, the implementation stage is a percentage of 78.18% which is included in the good category, the evaluation stage is a percentage of 77.55% which is included in the good category, and the evaluation of e-learning lecture media percentage of 74.58% entered into the good category. Overall the lecture process has been going well and e-learning can be an intermediary for delivering good material in online lectures. Keywords: Physical Sport and Health Learning, e-learning